Complement factor H attenuates TNF-α-induced inflammation by upregulating EIF3C in rheumatoid arthritis - Jia, Yimeng; Feng, Bin; Ji, Xin; Tian, Xinping; Zhao, Lidan; Zhou, Jiaxin; Zhang, Wen; Li, Mengtao; Fei, Yunyun; Wu, Xunyao (Journal of translational medicine, 2023)
To explore the role and underlying mechanism of Complement Factor H (CFH) in the peripheral and joint inflammation of RA patients. The levels of CFH in the serum and synovial fluid were determined by ELISA. The pyroptosis of monocytes was determined by western blotting and flow cytometry. The inflammation cytokine release was tested by ELISA. The cell migration and invasion ability of fibroblast-like synoviocytes (FLS) were tested by Wound healing Assay and transwell assay, respectively. The potential target of CFH was identified by RNA sequencing. CFH levels were significantly elevated in the serum and synovial fluid from RA and associated with high sensitivity C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), and disease activity score 28 (DAS28). TNF-α could inhibit CFH expression, and CFH combined with TNF-α significantly decreased cell death, cleaved-caspase 3, gasdermin E N-terminal (GSDME-N), and inflammatory cytokines release (IL-1β and IL-6) of RA-derived monocytes. Stimulated with TNF-α increased CFH levels in RA FLS and CFH inhibits the migration, invasion, and TNF-α-induced production of inflammatory mediators, including proinflammatory cytokines (IL-6, IL-8) as well as matrix metalloproteinases (MMPs, MMP1 and MMP3) of RA FLSs. The RNA-seq results showed that CFH treatment induced upregulation of eukaryotic translation initiation factor 3 (EIF3C) in both RA monocytes and FLS. The migration of RA FLSs was promoted and the expressions of IL-6, IL-8, and MMP-3 were enhanced upon EIF3C knockdown under the stimulation of CFH combined with TNF-α. In conclusion, we have unfolded the anti-inflammatory roles of CFH in the peripheral and joints of RA, which might provide a potential therapeutic target for RA patients.